2018
DOI: 10.1002/jac5.1056
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist authorship on clinical practice guidelines

Abstract: Introduction The National Academy of Medicine (NAM; formerly the Institute of Medicine) recommends multidisciplinary authorship as a standard for developing trustworthy guideline panels. The purpose of this study is to describe pharmacist authorship on clinical practice guideline (CPG) expert panels. Methods Guidelines published between January 1, 2010 and December 31, 2016 and were available in the Agency for Healthcare Research and Quality National Guideline Clearinghouse database were eligible for study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…When excluding Clinical Pharmacogenomic Implementation Consortium and Veterans Affairs/Department of Defense guidelines, which have universal pharmacist participation, only 20% of national guidelines across a spectrum of disciplines include a pharmacist author [ 8 ]. Notably, high-impact guidelines such as the International Antiviral Society-USA Panel guidelines on treatment and prevention of HIV in adults and the updated Surviving Sepsis guidelines do not have pharmacist members on the expert panel despite numerous pharmacotherapeutic recommendations and recognized contributions of pharmacists in these specialty areas [ 8 , 9 ]. Not surprisingly, the antimicrobial use category within the IDSA had the highest rate of pharmacist authorship, albeit with small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…When excluding Clinical Pharmacogenomic Implementation Consortium and Veterans Affairs/Department of Defense guidelines, which have universal pharmacist participation, only 20% of national guidelines across a spectrum of disciplines include a pharmacist author [ 8 ]. Notably, high-impact guidelines such as the International Antiviral Society-USA Panel guidelines on treatment and prevention of HIV in adults and the updated Surviving Sepsis guidelines do not have pharmacist members on the expert panel despite numerous pharmacotherapeutic recommendations and recognized contributions of pharmacists in these specialty areas [ 8 , 9 ]. Not surprisingly, the antimicrobial use category within the IDSA had the highest rate of pharmacist authorship, albeit with small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…As explicit previously, pharmacists play an elementary role in the development and implementation of institutional and national guidelines, protocols, and clinical pathways (Thompkins et al, 2019). The previous proof showed that 50% of the printed clinical follow guidelines between Jan 1, 2010, and Dec 31, 2016, had a minimum of one healthcare provider as a member of its writing panel (Thompkins et al, 2019). Pharmacists' interventions and involvement are related to higher rates of adherence to these clinical follow tips (Horning et al, 2007).…”
Section: Recommendationsmentioning
confidence: 89%
“…Pharmacists ought to take a proactive role in the development, implementation, and adherence to institutional and national tips concerning the emerging happening appreciate COVID-19. As explicit previously, pharmacists play an elementary role in the development and implementation of institutional and national guidelines, protocols, and clinical pathways (Thompkins et al, 2019). The previous proof showed that 50% of the printed clinical follow guidelines between Jan 1, 2010, and Dec 31, 2016, had a minimum of one healthcare provider as a member of its writing panel (Thompkins et al, 2019).…”
Section: Recommendationsmentioning
confidence: 90%
“…Unsurprisingly, only one author of the ACG CPG has an infectious diseases background and only one author of the IDSA/SHEA CPG has a gastroenterology background. The authors of each CPG are represented by both physicians and pharmacists, which provides a value-added expert level review [ 15 , 16 ].…”
Section: Guideline Highlightsmentioning
confidence: 99%